Safety of titanium dioxide (E171) as a food additive for humans - Warheit, David B. (Frontiers in Toxicology, 2024)
In May 2021, the European Food Safety Authority (EFSA) expert panel in evaluating the safety of TiO2 (E171) as a food additive, concluded that a concern for genotoxicity could not be ruled out. EFSA based this new interpretation on the results of genotoxicity tests of TiO2 nanomaterials. EFSA noted that available data are insufficient to define threshold doses/concentrations of TiO2 particles below which genotoxicity will not occur in tissues containing these particles.In this critique, it is demonstrated that EFSA made a manifest error regarding the safety of titanium dioxide (E171) particles as a food additive for humans. Titanium dioxide (TiO2), also known as E171, is very commonly used as a white colorant in food, pharmaceuticals, cosmetics, and toothpaste. First, the changing opinions from the various EFSA evaluations are noted, i.e., the changing opinions from EFSA in previous years vs. 2021. 2) low toxicity of TiO2 particles is described in rats exposed by oral gavage and feeding studies -in acute-subchronic -one generation 2 reproductive and chronic toxicity studies in rats and mice; -3) other international health scientists have weighed in on the EFSA (2021) decision and generally disagreed with EFSA's opinion on the safety of E171 TiO2. A common theme from the UK, Health Canada, and Australia-New Zealand Health Scientists is that it is inappropriate to compare nanoparticle toxicity studies (of dispersed/sonicated nanoparticles with the content of E171 TiO2 in foods -because the test materials used in key studies considered by EFSA ( 2021) are not representative of E171 TiO2 particles.